FACTORS INFLUENCING TAX AVOIDANCE: AN EMPIRICAL ANALYSIS OF INTERNAL CORPORATE ELEMENTS - Yulanda Dwi Cahyaningrum; Erida Herlina (Reviu Accounting, Business & Organizations, 2025)
Research Objective - This study aims to examine and analyze the effect of leverage, firm size, inventory intensity, and sales growth on tax avoidance. Method - The data analysis technique used in this study is multiple linear regression, with SPSS 25 as the testing tool. Findings - The results of this study indicate that leverage and inventory intensity have a positive effect on tax avoidance, firm size has a negative effect on tax avoidance, while sales growth has no effect on tax avoidance. Theoretical and Policy Implications - Agency theory is strengthened (because leverage and inventory intensity have a positive effect on tax avoidance), and signaling theory is supported (firm size has a negative effect on tax avoidance). Research Novelty - This study uses inventory intensity, a variable that has not been widely used as a primary variable in similar studies.